Accuracy of Cardiac Innervation Scintigraphy for Mild Cognitive Impairment With Lewy Bodies. (8th June 2021) - Roberts, Gemma; Durcan, Rory; Donaghy, Paul C.; Lawley, Sarah; Ciafone, Joanna; Hamilton, Calum A.; Colloby, Sean J.; Firbank, Michael J.; Allan, Louise; Barnett, Nicola; Barker, Sally; Howe, Kim; et al.
Abstract : Objective: To provide evidence that cardiac I-123-metaiodobenzylguanidine sympathetic innervation imaging (MIBG) scintigraphy differentiates probable mild cognitive impairment with Lewy bodies (MCI-LB) from mild cognitive impairment due to Alzheimer disease (MCI-AD), we scanned patients with MCI and obtained consensus clinical diagnoses of their MCI subtype. We also performed baseline FP-CIT scans to compare the accuracy of MIBG and FP-CIT. Methods: We conducted a prospective cohort study into the accuracy of cardiac MIBG scintigraphy in the diagnosis of MCI-LB. Follow-up clinical assessment was used to diagnose MCI-AD (no core features of MCI-LB and normal FP-CIT), probable MCI-LB (2 or more core features, or 1 core feature with abnormal FP-CIT), or possible MCI-LB (1 core feature or abnormal FP-CIT). For the comparison between MIBG and FP-CIT, only core clinical features were used for diagnosis. Results: We recruited 95 people with mild cognitive impairment. Cardiac MIBG was abnormal in 22/37 probable and 2/15 possible MCI-LB cases and normal in 38/43 MCI-AD cases. The sensitivity in probable MCI-LB was 59% (95% confidence interval [CI], 42%–75%), specificity 88% (75%–96%), and accuracy 75% (64%–84%). The positive likelihood ratio was 5.1 and negative likelihood ratio 0.46. With symptom-only diagnoses, the accuracies were 79% for MIBG (95% CI, 68%–87%) and 76% for FP-CIT (95% CI, 65%–85%). Conclusions: Cardiac MIBG appears useful in early disease, with an abnormal scan highly suggestive of MCI-LB. Validation in a multicenter setting is justified. Classification of Evidence: This study provides Class I evidence that cardiac MIBG distinguishes MCI-LB from MCI-AD.